CSC783: Component Based Software Engineering / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2018)
The course begins by discussing fundamental issues in building large scale systems. It then describes that these systems can be configured from the ‘federation’ of software components. The potential benefits of component-based such as reduce time-to-market, improve quality, reliability, ease of maintenance and flexibility are also discussed.